EVALUASI KUALITAS PEMBELAJARAN DARING PADA MAHASISWA UNIVERSITAS WIDYA GAMA MAHAKAM SAMARINDA - Suyanto Suyanto; Rini Rini (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2022)
Since the COVID-19 pandemic entered East Kalimantan, the strategy of studying at home was considered the right step to reduce the spread of COVID-19 among students. The sudden change of face-to-face learning to online learning makes learning unable to run optimally and requires adjustments from various aspects. Widya Gama Mahakam University Samarinda with various constraints and conditions that are limited to the devices owned by students also conduct online learning. The purpose of this study was to measure the level of student satisfaction during online learning during the COVID-19 pandemic using the Service Quality (Servqual) and Importance Performance Analysis (IPA) methods. Servqual and IPA are methods to measure the level of satisfaction and quality of a service. The results showed that all dimensions in the study were declared valid and reliable because all of the above were from the minimum tolerable standard. There are 3 dimensions that are in quadrant A, namely high expectations while the perceived reality is low so it is necessary to improve lecturer performance, 5 dimensions in quadrant B, namely high expectations and high reality so that they need to be maintained and 6 which are in quadrant C, namely low expectations and low reality, which means that improvements must be made and 3 dimensions in quadrant D, namely low expectations and high reality, this needs to be evaluated and reduced on things that can encourage the achievement of efficiency in the online learning process.